E-Archive Academic Data at SMK Negeri 2 Sekayu - Handayani, Fitri Kurnia; Megawaty (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Effective management of archival documents is vital in the educational sector as it plays a crucial role in decision-making and preserving historical records. Archives are a valuable resource that contains a wealth of information for any organization. However, the traditional method of physical document management at Sekayu 2 Negeri Vocational School has led to a significant accumulation of documents, making the process both ineffective and inefficient. This situation has created an urgent need for faster access to information. To address this issue, the school has developed an Electronic Archive for Academic Data that aims to streamline the archiving process, making it more efficient and effective. The primary objectives of this initiative are to facilitate faster retrieval of information and to reduce the physical storage space required for documents. The E-Archive for Academic Data at Sekayu 2 Negeri Vocational School was developed using the PHP programming language and the MySQL database. The introduction of this digital filing system is expected to significantly reduce the time needed to access archives and decrease the physical storage space required, thereby enhancing efficiency and effectiveness at SMK Negeri 2 Sekayu.